How do teachers evaluate their parent communication competence? Latent profiles and relationships to workplace behaviors. (April 2016) - Gartmeier, Martin; Gebhardt, Markus; Dotger, Benjamin
Abstract: Parent-teacher communication competence, frequency of exchange on parent-related issues with colleagues and time spent working with parents were measured with questionnaires in a sample of 677 German mathematics teachers. A latent class analysis revealed four groups of teachers: 24% showed high, 36% showed medium and 16% showed lower levels of communication competence with balanced profiles. A fourth profile (24%) showed a strong focus on pragmatic problem solving in communication with parents. The profiles differed in the extent of their exchange with colleagues on parent-related issues. No relationships were found regarding the time spent talking to parents. Highlights: 677 German mathematics-teachers evaluated their parent communication competence. 24% showed high, 36% medium and 16% showed lower competence with balanced profiles. 24% exhibited a focus on problem solving in communication with parents. Higher competence related to more exchange with colleagues on parent-issues. Competence did not relate to time spent working with parents.